Roundtrip Migration Processes. Orality and Written Transposition in the Memoirs of an Anti-Franco Militant: David Álvarez Carballido. From Galicia to Argentina (and vice versa) - Sánchez, Mariela (Madrygal. Revista de Estudios Gallegos, 2020)
This paper exposes different aspects and theoretical problematizations in relation to an editing process conducted on the basis of a series of oral interviews carried out in the 90s by Antón Santamarina, the selection published in homage to Xesús Alonso Montero and the meeting, by Anahí Almasia, in 2016, from these sources that featured David Álvarez Carballido as the protagonist (A Fonsagrada, 1922-2017). The material under analysis includes the Galician-language narrative of a personal / family history that involves a referential framework illustrating the fundamental historical and political vicissitudes of Galicia and Argentina throughout most of the 20th century, as well as aspects of migratory processes and experiences of repression and confinement recognizable in other latitudes. I will analyze the book transposition operations of the aforementioned supports and the theoretical foundations taken into account in the editing process in which I participated.